2003
DOI: 10.1089/107632703768247430
|View full text |Cite
|
Sign up to set email alerts
|

Liver Tissue Engineering within Alginate Scaffolds: Effects of Cell-Seeding Density on Hepatocyte Viability, Morphology, and Function

Abstract: Tissue engineering with three-dimensional biomaterials represents a promising approach for developing hepatic tissue to replace the function of a failing liver. Herein, we address cell seeding and distribution within porous alginate scaffolds, which represent a new type of porous biomaterial for tissue engineering. The hydrophilic nature of the alginate scaffold as well as its pore structure and interconnectivity enabled the efficient seeding of hepatocytes into the scaffolds, that is, 70-90% of the initial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(151 citation statements)
references
References 30 publications
6
143
0
2
Order By: Relevance
“…In the present study, the viability of cells in the centre of both 2 and 5% w/v alginate hydrogel beads of 3-mm diameter was observed ( Fig. 1) It is proposed that the lack of mitotic activity is due in part to the use of a relatively low cell-seeding density [35], the encapsulation of dispersed cells rather than spheroids [36], the use of a non-liquefied core [37] and the use of high concentrations of alginate, which resulted in the fibroblasts being mechanically confined from each other by cross-linked chains of alginate. These results demonstrate that encapsulation in alginate effectively mitotically inhibits the fibroblasts without the need for treatment with Mitomycin C or gamma-irradiation, to allow for co-culturing of keratinocytes with the fibroblasts.…”
Section: Resultssupporting
confidence: 56%
“…In the present study, the viability of cells in the centre of both 2 and 5% w/v alginate hydrogel beads of 3-mm diameter was observed ( Fig. 1) It is proposed that the lack of mitotic activity is due in part to the use of a relatively low cell-seeding density [35], the encapsulation of dispersed cells rather than spheroids [36], the use of a non-liquefied core [37] and the use of high concentrations of alginate, which resulted in the fibroblasts being mechanically confined from each other by cross-linked chains of alginate. These results demonstrate that encapsulation in alginate effectively mitotically inhibits the fibroblasts without the need for treatment with Mitomycin C or gamma-irradiation, to allow for co-culturing of keratinocytes with the fibroblasts.…”
Section: Resultssupporting
confidence: 56%
“…Hepatocytes were seeded on three gNWF disks and cultured for 10 days in the bioreactor to determine non-destructive cell release at 20°C. To determine cell viability, cells were stained with fluorescein diacetate, which is essentially converted into fluorescein, a green fluorescent compound, by viable cells only [38]. Fig.…”
Section: Temperature-induced Cell Releasementioning
confidence: 99%
“…Previously, the active interaction between collagen and the embedded cells was assumed to enhance cellular functions (Wu et al 1996;Yamada et al 2001) and, furthermore, high cell density culture was highly suggested to enhance cell viability and hepatocellular functions such as albumin and urea secretion and detoxification (Dvir-Ginzberg et al 2003). Nevertheless, in this paper, the non-correlation between gel contraction and cell activity was unexpectedly concluded as a result of the fact that cell viability as well as liver-specific functions per viable cell were lower in the gel entrapment cultures at higher cell densities regardless of the more severe gel contraction observed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high cell density as well as high cellular functions were required for clinical use of BAL and in vitro model of drug screening platform. Dvir-Ginzberg et al (2003) adopted alginate scaffolds with high porosity and large pore sizes to improve mass transfer for sustaining high cell viability under high cell loading. In consideration of the adverse effect of gel contraction on cellular functions, we strongly recommend that gel contraction should be avoided due to its negative effect on mass transfer.…”
Section: Discussionmentioning
confidence: 99%